Developmental changes in fact and source recall: Contributions from executive function and brain electrical activity - Vinaya Rajan; Martha Ann Bell (Developmental Cognitive Neuroscience, 2015)
Source memory involves recollecting the contextual details surrounding a memory episode. When source information is bound together, it makes a memory episodic in nature. Unfortunately, very little is known about the factors that contribute to its formation in early development. This study examined the development of source memory in middle childhood. Measures of executive function were examined as potential sources of variation in fact and source recall. Continuous electroencephalogram (EEG) measures were collected during baseline and fact and source retrieval in order to examine memory-related changes in EEG power. Six and 8-year-old children were taught 10 novel facts from two different sources and recall for fact and source information was later tested. Older children were better on fact recall, but both ages were comparable on source recall. However, source recall performance was poor at both ages, suggesting that this ability continues to develop beyond middle childhood. Regression analyses revealed that executive function uniquely predicted variance in source recall performance. Task-related increases in theta power were observed at frontal, temporal and parietal electrode sites during fact and source retrieval. This investigation contributes to our understanding of age-related differences in source memory processing in middle childhood.